Achieving sustainability and scalability of a large-scale prenatal cash and food transfer intervention in Bangladesh - Akter, Fahmida; Parvin, Aklima; Roy, Shalini; Frongillo, Edward A.; Leroy, Jef L.; Larson, Leila M. (Elsevier, 2024)
Objectives: The WHO (2016) antenatal care guidelines recommend research on alternatives to prenatal energy and protein supplements – such as cash or food distribution. The Bangladesh government is currently implementing the Mother and Child Benefit Programme (MCBP) to improve prenatal nutrition and child health. We conducted implementation research that aimed to understand how the MCBP, and augmented versions of it, 1) stimulated behavior changes, 2) enabled or prevented participants to sustain behavior changes, and 3) achieved conditions required for program scale-up.